BUSINESS EDUCATION INDUSTRY PREPARING FOR EDUCATION 4.0 - PRAKASH HEMRAJ KARMADKAR; D. Lit (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The threshold of a technological revolution that will vitally alter the way human live, work, and relate to one another. In its scale, scope, and complexity, the transformation will be unlike anything humankind has experienced before. We do not yet know just how it will unfold, but one thing is clear: the response to it must be integrated and comprehensive, involving all stakeholders of the global polity, from the public and private sectors to academia and civil society.